Vibration Characteristics of Force Signal for Single Diamond Grit Scratching Process - Wu, Haiyong (Manufacturing Technology Journal, 2020)
Scratching force is a significant factor to evaluate the characteristics of single diamond grit scratching process. In this paper, experimental study was carried out to investigate the vibration characteristics of force signals during the scratching process. A precise multicomponent dynamometer is employed in the force measurement during a single diamond grit scratching on pure copper. The frequencies of the vibration section of force signals with different scratching parameters are calculated and analyzed. The influence of force signal vibration on the measuring accuracy of dynamometer is systematically analyzed further. The results show that higher scratching speed and larger scratching depth lead to larger vibration amplitudes of the force signals. Strong impact on the quartz piezoelectric crystal of dynamometer, which is produced indirectly by single diamond grit scratching process, leads to the vibration of scratching force signal. The first semi-sinusoidal force signal is the actual scratching force. The vibration of the scratching force signal has little effect on the measuring accuracy of the dynamometer.
Keywords: Single Diamond Grit; Scratching; Force Signal; Signal Vibration